Ultra Structural Analysis and Lipid Staining of Biodiesel Producing Microalgae - Chlorella vulgaris Collected from Various Ponds in Tamil Nadu, India - N. Senthil Kumar, S. Elumalai*, S. Baskaran, V. Prakasam, (Journal of Ecobiotechnology, 2011)
The present research paper describes to evaluate 10 different Microalgal lipid contents by Nile red and Bodipy staining. The ultra structural studies carried out by Scanning Electron Microscope (SEM). The micro algal samples were collected from province of Tamil Nadu, located in Southern India.Ã‚Â Compare to Nile Red stain Bodipy is a specific stain for to detect lipid content present in the living algal cells. In this study clearly describe Chlorella vulgaris stained by Bodipy have shown more lipid content than other microalgae collected from various location.